(untitled) (LACCEI, 2024)
The covid 19 pandemic has led to various changes and an imminent adaptation, present in all sectors. One of them is education, by transferring the teaching-learning process from faceto-face classrooms to virtual ones, in this way university professors had to couple ICT (Information and Communication Technologies) to their methodologies, adopting or strengthening skills muchneeded digital tools in today’s world. The main objective of the research was focused on determining the level of digital skills that teachers of a Public University have using a quantitative approach of non-experimental cross-sectional design and with a descriptive level. The most outstanding findings are that more than half of the teachers have a level achieved in the five dimensions of digital skills however, there is more than a third that requires strengthening the dimension of content creation, stressing that in public universities the management of virtual academic resources It was a key element to safeguard the teaching of classes in times of pandemic, limiting only the basic knowledge and management of these tools. Likewise, there is no direct relationship between the level achieved and the number of training sessions, since the less training carried out, the higher the level of achievement. Currently, promoting digital skills in all professionals, even more so in university teachers, favors interaction with the technological vanguard.